Respiratory pathology in the mdx/utrn -/- mouse: A murine model for Duchenne Muscular Dystrophy (DMD). - Marán Y Hernández Rodríguez; Debolina D Biswas; Aoife D Slyne; Jane Lee; Evelyn Scarrow; Sarra M Abdelbarr; Heather Daniels; Ken D O'Halloran; Leonardo F Ferreira; Charles A Gersbach; Mai K ElMallah (PLoS ONE)
Duchenne muscular dystrophy (DMD) is an X-linked devastating disease caused by a lack of dystrophin which results in progressive muscle weakness. As muscle weakness progresses, respiratory insufficiency and hypoventilation result in significant morbidity and mortality. The most studied DMD mouse model- the mdx mouse- has a milder respiratory phenotype compared to humans, likely due to compensatory overexpression of utrophin. mdx/utrn-/- mice lack both dystrophin and utrophin proteins. These mice have an early onset of muscular dystrophy, severe muscle weakness, and premature death, but the respiratory pathophysiology is unclear. The objective of this study is to characterize the respiratory pathophysiology and histopathology using whole body plethysmography to measure breathing and metabolism, diaphragm muscle functional analysis, histology, and immunohistochemistry. The mdx/utrn-/- mice have significant respiratory and metabolic deficits with respiratory insufficiency and hypoventilation when exposed to hypoxia and hypercarbia as early as 6 weeks of age. They also have significant diaphragmatic weakness and disrupted diaphragmatic structural pathology. The mdx/utrn-/- mice display respiratory dysfunction that mimics the DMD phenotype and therefore can provide a useful model to study the impact of novel therapies on respiratory function for DMD.